Dissolved ozone flotation-nucleation crystallization pelleting process for the treatment and reclamation of oil and gas field produced water - SONG Ji’na; YUE Wen; TONG Xiao; XU Lanzhou; WANG Yadong; SHANG Yabo; JIN Xin; JIN Pengkang (Gongye shui chuli)
To solve the difficult problems of large volume and complex water quality in oil and gas fields, and to achieve the goal of reusing oil and gas field produced water after treatment, a combination process of dissolved ozone flotation-nucleation crystallization pelleting was proposed. The treated produced water could meet the water quality requirements for preparing guanidine fracturing fluid. Taking COD and SS removal rates as the evaluation indexes, the two processes of pre-oxidation-coagulation and dissolved ozone flotation were compared. The results showed that the dissolved ozone flotation process had better effect on COD and SS removal, and the removal rates could reach 59% and 88%, respectively. Both COD and SS met the water quality requirements for preparing guanidine fracturing fluid. Taking the removal rates of Ca2+ and Mg2+ as the hardness index, the removal performance of nucleation crystallization pelleting process and chemical precipitation process were compared. The results showed that the nucleation crystallization pelleting process had significant advantages in hardness removal, with a total removal efficiency of Ca2+ and Mg2+ at 86%, achieving the requirements for preparing guanidine fracturing fluid. Taking the produced water from four stations in Changqing Oilfield as the actual treatment object, the guanidine fracturing fluid, prepared from the produced water treated by dissolved ozone flotation-nucleation crystallization pelleting process, showed good viscosity of the base fluid, which could be lifted and not easily broken. The dissolved ozone flotation-nucleation crystallization pelleting process could not only achieve the resource utilization of produced water, but also reduce the daily production costs, with good economic and environmental benefits. Therefore, the combination process could provide technical reference for the oil and gas field produced water reclamation.